2016
DOI: 10.1128/mcb.00534-15
|View full text |Cite
|
Sign up to set email alerts
|

Autism-Associated Chromatin Regulator Brg1/SmarcA4 Is Required for Synapse Development and Myocyte Enhancer Factor 2-Mediated Synapse Remodeling

Abstract: Synapse development requires normal neuronal activities and the precise expression of synapse-related genes. Dysregulation of synaptic genes results in neurological diseases such as autism spectrum disorders (ASD). Mutations in genes encoding chromatin-remodeling factor Brg1/SmarcA4 and its associated proteins are the genetic causes of several developmental diseases with neurological defects and autistic symptoms. Recent large-scale genomic studies predicted Brg1/SmarcA4 as one of the key nodes of the ASD gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 64 publications
2
39
0
Order By: Relevance
“…These factors may be functionally related because SMARCA4 is a coregulator for many of these factors. MEF2C has been shown to interact with SMARCA4 and is required for the activity-dependent recruitment of SMARCA4 to its target regions (Zhang et al 2015). Moreover, USF1/2 can bind a SMARCA4-associated factor, SMARCD3, and recruit other BAF subunits including SMARCA4 (Wang and Sul 1997).…”
Section: Smarca4 Globally Affects Gene Regulation In Mcf-10a Cellsmentioning
confidence: 99%
“…These factors may be functionally related because SMARCA4 is a coregulator for many of these factors. MEF2C has been shown to interact with SMARCA4 and is required for the activity-dependent recruitment of SMARCA4 to its target regions (Zhang et al 2015). Moreover, USF1/2 can bind a SMARCA4-associated factor, SMARCD3, and recruit other BAF subunits including SMARCA4 (Wang and Sul 1997).…”
Section: Smarca4 Globally Affects Gene Regulation In Mcf-10a Cellsmentioning
confidence: 99%
“…Brm with transcriptional factors downstream of MAPK/ERK signaling, such as Pnt or Aop, constituting a positive auto-regulation feedback loop. Alternative mechanisms await further investigation to elucidate the effects of Brm.Our finding that Brm inactivation protects DA degeneration seems to be at odds with the positive roles of Brm in the neural development[15,16,33]. However, previous studies have shown SWI/SNF complexes in different tissues at different stages have distinct functions byeliciting context-specific transcription programs.…”
mentioning
confidence: 64%
“…Brm was found here to be progressively up-regulated in the aging brains of PD fly models. One possibility is through a genetic imprinting response to elevated calcium level triggered by aberrant neuronal activities or calcium metabolism [33]. Alternatively, Brm could be activated through NF-kB mediated inflammatory responses that are well recognized in the development of neurodegenerative diseases [34].…”
Section: Discussionmentioning
confidence: 99%
“…Variants enriched in ASD are found in genes that regulate synaptogenesis [De Rubeis et al, ; Patel, Ioannidis, Cullen, & Rehkopf, ], cell migration [Boitard et al, ; Reiner, Karzbrun, Kshirsagar, & Kaibuchi, ; Wang et al, ; Wong et al, ], dendritic growth [De Rubeis et al, ] as well as more basic functions such as chromatin remodeling, cell signaling and cell cycle regulation [Anney et al, ; De Rubeis et al, ]. Transcriptomics along with whole exome sequencing of histone modifying genes similarly suggest altered expression of genes involved in synapse formation, neuronal connectivity, and apoptosis [De Rubeis et al, ; Mahfouz, Ziats, Rennert, Lelieveldt, & Reinders, ; Zeidan‐Chulia et al, ; Zhang et al, ]. Gene expression is regulated by epigenetic changes, which in turn may have environmental origins.…”
Section: Concepts Of Causationmentioning
confidence: 99%